Assessment of School Vegetable Gardens in Selected Deped Schools in Ilocos Sur, Philippines: Building Food Literacy Through Gardening and Educatio - Dela Cruz, Mr. Richard D.; D. Abella, Dr. Analyn; L. Hayohay, Dr. Cherisse May; O. Menor, Dr. Mary Ruth; Naungayan, Dr. Juvy D.; Naungayan , Mr. Albert G. (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: The Department of Education (DepEd) in the Philippines has prioritized school food production programs through policies that encourage schools to establish vegetable gardens to supplement meals and teach agricultural skills. Ilocos Sur, a province in Northern Luzon, has a strong agricultural heritage and has adopted such initiatives, but limited data exist on their impact on food literacy among students. Methods: This mixed-method study assessed school vegetable garden initiatives in 12 selected DepEd elementary and secondary schools in Ilocos Sur Philippines, to determine their role in building food literacy among Grade 4-10 students (n=360) during the 2023-2024 academic year. Food literacy was measured across three domains, which are nutritional knowledge, agricultural skills, and dietary behavior. Quantitative data were collected via pre- and post tests, and qualitative data were gathered through focus group discussions with students, teachers, and parent stakeholders (n=48), field observation, and document reviews. Results: Findings revealed significant improvements in all food literacy domains where nutritional knowledge had a pre-test mean of 12.1, post-test mean of 16.9, p-value is less than 0.001; agricultural skills had a pre-test mean of 8.5, post-test mean of 11.6, p-value is less than 0.001; and dietary behavior had a pre-test mean of 8.9, post-test mean of 11.6, p-value is less than 0.001. Rural students and secondary students showed higher gains than their urban and elementary counterparts. Qualitative findings highlighted successful strategies like stakeholder collaboration and teacher training, alongside challenges including resource constraints and sustainability gaps.